2022
DOI: 10.1155/2022/7420507
|View full text |Cite
|
Sign up to set email alerts
|

Celastrol Protects against Cerebral Ischemia/Reperfusion Injury in Mice by Inhibiting Glycolysis through Targeting HIF-1α/PDK1 Axis

Abstract: Cerebral ischemia/reperfusion (I/R) injury is closely related to dysfunctional glucose metabolism. Celastrol is a bioactive compound that has been found to exhibit neuroprotective effects in cerebral ischemia, while whether it can protect against cerebral I/R injury by regulating glycolysis remains unclear. The goal of this study is to investigate the role of celastrol on cerebral I/R injury and its underlying mechanisms in transient middle cerebral artery occlusion (tMCAO) mice. Methods. To observe the protec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 52 publications
1
9
0
Order By: Relevance
“…In addition, glycolysis plays a role in the pathogenesis of cerebral ischemia, and some studies have found that inhibition of excessive glycolysis can protect neurons against OGD ( Burmistrova et al, 2019 ; Vojinovic et al, 2020 ). Chen et al reported that celastrol inhibited hypoxia inducible factor-1α (HIF-1α)/pyruvate dehydrogenasekinase1 (PDK1), thus attenuating glycolysis and exerting neuroprotection ( Chen et al, 2022 ). Besides that, studies of long noncoding RNAs (LncRNAs) have received much attention in recent years.…”
Section: Effects Of Triptolide and Celastrol On Brain And Spinal Cord...mentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, glycolysis plays a role in the pathogenesis of cerebral ischemia, and some studies have found that inhibition of excessive glycolysis can protect neurons against OGD ( Burmistrova et al, 2019 ; Vojinovic et al, 2020 ). Chen et al reported that celastrol inhibited hypoxia inducible factor-1α (HIF-1α)/pyruvate dehydrogenasekinase1 (PDK1), thus attenuating glycolysis and exerting neuroprotection ( Chen et al, 2022 ). Besides that, studies of long noncoding RNAs (LncRNAs) have received much attention in recent years.…”
Section: Effects Of Triptolide and Celastrol On Brain And Spinal Cord...mentioning
confidence: 99%
“…attenuating glycolysis. Celastrol attenuates glycolysis and exerts neuroprotection by inhibiting HIF-1α/PDK1 pathway ( Chen et al, 2022 ), e). suppressing NOX activation and rapid H 2 O 2 release.…”
Section: Molecular Mechanisms Of Triptolide and Celastrol For Therape...mentioning
confidence: 99%
“…Mice were re-anesthetized and sacrificed 24 h after tMCAO. The concentration of celastrol used in the experiment was based on the concentration reported in previous study ( Chen et al, 2022 ).…”
Section: Methodsmentioning
confidence: 99%
“…The primer sequences (Sangon Biotech) are clarified in Table 1 . Gene expression was assessed by the 2 −ΔΔCt method [ 30 ].…”
Section: Methodsmentioning
confidence: 99%